Clinicopathological features and surgical treatment of cervical oesophageal cancer - Shao-bin Chen (Nature Portfolio, 2017)
Abstract Cervical oesophageal cancer (CEC) is a relatively uncommon malignancy. The biological behaviour and treatment have not been well studied. This retrospective study reviewed the clinicopathological features of 28 patients with CEC who underwent surgical resection to investigate the biological behaviour, treatment and prognosis of CEC. The long-term outcomes of these patients were compared with those of the CEC patients who received definitive chemoradiotherapy and those of thoracic or abdominal oesophageal cancer patients who underwent surgery. The study group contained 21 men and 7 women, ranging in age from 41 to 67 years (median: 56.5 years). The median survival time and the 1-, 3-, and 5-year overall survival rates were 25.0 months, 83.8%, 48.8%, and 41.9%, respectively. Only salvage surgery was found to affect the overall survival (P = 0.007). The long-term outcomes for CEC patients who underwent surgery were significantly better than those who received definitive chemoradiotherapy (P = 0.045) but were similar to those of thoracic or abdominal oesophageal cancer patients. In summary, CEC is an uncommon and aggressive malignancy. The malignant potential of CEC is similar to that of thoracic or abdominal oesophageal cancer. Surgical resection is an important therapeutic strategy and may be associated with better survival rates than definitive chemoradiotherapy.